2014
DOI: 10.1111/ajt.12757
|View full text |Cite
|
Sign up to set email alerts
|

DAP12 Deficiency in Liver Allografts Results in Enhanced Donor DC Migration, Augmented Effector T Cell Responses and Abrogation of Transplant Tolerance

Abstract: Liver interstitial dendritic cells (DC) have been implicated in immune regulation and tolerance induction. We found that the transmembrane immuno-adaptor DNAX-activating protein of 12kDa (DAP12) negatively regulated conventional liver myeloid (m) DC maturation and their in vivo migratory and T cell allostimulatory ability. Livers were transplanted from C57BL/6(H2b) (B6) wild-type (wt) or DAP12−/− mice into wt C3H (H2k) recipients. Donor mDC (H2-Kb+CD11c+) were quantified in spleens by flow cytometry. Anti-dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 80 publications
2
38
0
Order By: Relevance
“…We have reported that, in vitro , DAP12 –/– or DAP12 small interfering RNA–treated liver DCs exhibited a more activated/mature phenotype and enhanced production of proinflammatory cytokines compared with WT liver DCs . When we examined the extent to which DAP12 regulated both major histocompatibility complex (MHC) Ⅱ (I‐A b and IA/IE) and costimulatory molecule expression by liver and spleen DCs following LPS stimulation in vivo , we found that the MFI of these molecules expressed by both liver and spleen DCs from LPS‐injected DAP12 –/– mice was increased compared with WT controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have reported that, in vitro , DAP12 –/– or DAP12 small interfering RNA–treated liver DCs exhibited a more activated/mature phenotype and enhanced production of proinflammatory cytokines compared with WT liver DCs . When we examined the extent to which DAP12 regulated both major histocompatibility complex (MHC) Ⅱ (I‐A b and IA/IE) and costimulatory molecule expression by liver and spleen DCs following LPS stimulation in vivo , we found that the MFI of these molecules expressed by both liver and spleen DCs from LPS‐injected DAP12 –/– mice was increased compared with WT controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For all (liver transplant) experiments, age‐matched animals were distributed randomly into experimental groups. Liver transplants were performed in male B6 donors to male C3H recipients because for anatomic/surgical reasons, male B6 (or B10) into male C3H is the model of choice for orthotopic allogeneic liver transplantation in the mouse . After surgery, each mouse was housed alone for the first week.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular mechanisms whereby liver APCs regulate/inhibit T cell responses include their expression of programed death ligand‐1 (PD‐L1 = B7 homologue 1 [B7‐H1]), interleukin (IL)‐10, FasL, the Notch ligand Jagged 1, CD39, and the immunoreceptor tyrosine‐based activation motif–bearing transmembrane adaptor protein DNAX‐activating protein of 12 kDa (DAP12) . Of these molecules, PD‐L1, IL‐10, and DAP12 have been implicated in the regulation of mouse “spontaneous” liver transplant tolerance …”
mentioning
confidence: 99%
“…A role for LPS-induced increased expression of DNAX-activating protein of 12 kDa (DAP12), which is associated with IDO induction, is pertinent in this regard as DAP12-deficient DCs exhibit enhanced maturation upon TLR ligation [105,106]. This mechanism may be an important part of the phenomenon known as "endotoxin tolerance" [107].…”
Section: Hsc-dc Interactionsmentioning
confidence: 99%